PROSES DAN HAMBATAN DALAM PENULISAN KONTEN DI SITUS WEB OLEH AGENSI PERIKLANAN DIGITAL - Maharani Imran (Prodi Ilmu Komunikasi Universitas Putera Batam, 2022)
Digital advertising agencies help brand owners manage and promote the brand over the internet so that the brand can persist and win the hearts of consumers by following trends or times. Content writers are needed to creatively shape ideas and concepts for a content to attract attention and influence the target audience. The purpose of this study is to describe the process and barriers of website content writing by digital advertising agencies. This study uses qualitative methods with a case study approach, data collection techniques using interviews, the data analysis techniques used in this study are thematic analysis. The outcome of this study is the process of writing website content by digital advertising agencies, consisting of obtaining keywords for articles from the management, collecting reference materials for articles related to the given keywords of articles, rewriting article content into new article content, paraphrasing the words in the article according to the received article keywords, checking articles using plagiarism checking software, sending article content to leaders and administrators for editing and for additional information in the form of interesting images related to the content of the created article, and uploading and publishing the articles on the website. From the results of this study, it is suggested that in the future, the keywords for the articles should be more diverse, the existing internet connection should be further improved, and the deadline for writing the website content should be weekly rather than daily.